On the empirics of capital accumulation and economic growth - Erich Gundlach (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
Recent advances in the theory of economic growth have led to a large number of competing endogenous-growth models. The empirical evidence presented in this paper supports the Rebelo (1991) growth model with constant returns to scale and constant returns to aggregate capital. For reasonable parameterizations, this model predicts that a one percentage point increase in the rate of investment in physical capital increases the growth rate by about 0.1 percentage points. The results do not support models which postulate diminishing returns to aggregate physical and human capital, externalities in the accumulation of physical capital, or aggregate economies of scale
Keywords: 330; Neue Wachstumstheorie; Investition; Theorie